Impact of diagnostic ureteroscopy before radical nephroureterectomy on intravesical recurrence in patients with upper tract urothelial cancer - Chung, Younsoo (Investig Clin Urol, 2020)
PURPOSE: To evaluate the impact of diagnostic ureteroscopy performed before radical nephroureterectomy (RNU) on intravesical recurrence (IVR) in patients with upper tract urothelial carcinoma (UTUC). MATERIALS AND METHODS: From May 2003 to December 2018, patients who underwent RNU for UTUC were enrolled and divided into two groups according to whether they underwent preoperative ureteroscopy (Pre-U vs. Non-U). We excluded patients who had a history of bladder cancer and did not receive bladder cuff resection during surgery. Perioperative parameters were compared between the two groups by use of t-tests or chi-square tests. Kaplan–Meier and Cox proportional hazards analyses were used to assess the association between Pre-U and IVR. RESULTS: Of the 453 total patients, 226 patients (49.9%, Pre-U group) had received diagnostic ureteroscopy before RNU, and 227 patients (50.1%, Non-U group) had not. IVR occurred in 99 patients (43.8%) in the Pre-U group and 61 patients (26.9%) in the Non-U group (p=0.001). The median time to recurrence was 107 months. The 5-year IVR-free survival rates were 56.2% and 73.1% in the Pre-U and Non-U groups, respectively (log rank test, p<0.001). Multivariate Cox proportional hazards analysis showed that Pre-U was a significant factor (hazard ratio, 1.413; 95% confidence interval, 1.015–1.965; p=0.040) after adjustment for other factors including tumor stage, location, etc. CONCLUSIONS: Preoperative diagnostic ureteroscopy before RNU was a significant factor for IVR. Therefore, we should carefully consider Pre-U before RNU for nonobvious ureteral lesions. These results should be validated in a prospective study.